Maternal gestational diabetes in singleton pregnancies conceived by ART may be modified by periconceptional B vitamins - Li, Minyu; Chen, Yanping; Wang, Yongxiang; Wang, Hong; Ding, Xueteng; Li, Guoju (Frontiers in Nutrition, 2023)
Background: The risk of maternal gestational diabetes mellitus (GDM) may be influenced by pregnancies conceived through assisted reproductive technology (ART). However, the influence of the dosage of B vitamins (folate, vitamin B6 and vitamin B12) on GDM weren’t considered. Thus, we hypothesized that periconceptional B vitamins could modify maternal GDM in singleton pregnancies conceived by ART. Methods: This study is a prospective cohort study using data from 3,252 women with singleton pregnancies and received a 75 g oral glucose tolerance test (OGTT) at 24-28 weeks of gestation. We included a interaction term in the multivariable logistic and linear regression models, respectively, to test our hypothesis. Results: Women who underwent ART were significantly associated with the incidence of GDM compared with spontaneous pregnancy women. The adjusted odds ratio (aOR) was 1.59, and the 95% confidence interval (CI) was 1.08-2.34. ART pregnancies also elevated OGTT (oral glucose tolerance test)1-h blood glucose levels and OGTT 2-h blood glucose levels (P < 0.05). A positive association between dietary vitamin B6 (aOR = 1.60, 95% CI: 1.13-2.27), dietary vitamin B12 (aOR = 1.88, 95% CI: 1.34-2.64) and dietary folate (aOR = 1.66, 95% CI: 1.19-2.32) with GDM risk comparing the highest to the lowest quartile (all Ptrend < 0.001). The aORs of GDM for inadequate (< 400 µg/day), adequate (400-800 µg/day), and excessive (> 800 µg/day) supplemental folate intake were 1.00, 0.93, and 1.30, respectively (Ptrend = 0.033). Since only the supplemental folate illustrates a statistically significant interaction with ART (P for interaction < 0.05), the association between ART and GDM and OGTT blood glucose levels stratifying by supplemental folate were further evaluated. These increased risks of GDM (aOR = 1.62, 95% CI: 1.39-3.39) and the regression coefficients () of 1-h blood glucose ( = 0.76, 95% CI: 0.39-1.13) and 2-hours blood glucose ( = 0.60, 95% CI: 0.29-0.92) in the multiple linear regression model were significant only in the ART group with excessive supplemental folate (> 800 µg/day). Conclusion: The risk of GDM is significantly elevated, particularly among those women who conceived ART with the intake of excessive supplemental folate (> 800 µg/day).